Scar Management in Pediatric Patients - Sydney Barone; Eric Bao; Stephanie Rothberg; Jose F. Palacios; Isabelle T. Smith; Neil Tanna; Nicholas Bastidas (Medicina)
Background and Objectives: Pediatric patients can acquire scars from both accidental injury and surgical procedures. While scars cannot be avoided if a full-thickness injury occurs, scar visibility may be minimized through a variety of approaches. In this narrative review, we evaluate the current evidence and propose an algorithm for scar management in pediatric patients. Materials and Methods: A review of the literature was performed for scar management techniques for pediatric patients. Management modalities based on the type of scar and dosing, treatment regimen, and safety profiles are described in this article and used to create a scar management algorithm. Results: The initial step to scar management in the pediatric population involves ensuring minimal wound tension, which can be achieved through making the incision along relaxed skin tension lines, and early, minimal tension wound closure. Subsequent treatments to optimize scar care should begin 2–3 weeks following wound closure and involve the application of silicone gel or sheets and scar massaging. When topical products are insufficient, laser therapy can be utilized for the management of immature erythematous or thick scars. When mature, pathological scars form such as atrophic scars, hyperpigmentation, hypertrophic scars, or keloids, a combination of modalities is recommended. These modalities vary by scar type and include retinoids and dermabrasion for atrophic scars; retinoids, hydroquinone, and laser therapy for hyperpigmentation; and pressure therapy, corticosteroids, and laser therapy for hypertrophic scars and keloids. When mature, pathological scars persist following 12 months of non-invasive therapies, surgical excision should be considered. Conclusions: Several treatment options are available to manage scars in the pediatric population depending on scar type.